2010
DOI: 10.1071/mf10113
|View full text |Cite
|
Sign up to set email alerts
|

Defining and using 'best available science': a policy conundrum for the management of aquatic ecosystems

Abstract: Integrative research has been the dominant theme in this Special Issue, demonstrated by contemporary examples of effective collaborations and solutions for the successful engagement of scientists in the policy and management arena. Evident in these papers is the increasing use of the term ‘best available science’ (BAS) as a basis for well-informed resource management decisions. The term is used to engender credibility and trust among stakeholders and promotes greater awareness, communication, involvement, tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 54 publications
0
59
0
1
Order By: Relevance
“…see Ryder et al 2010). Until we have the additional and targeted investment to support an appropriate level of fundamental and applied research into the ecology and management of our coastal temperate wetlands, it is difficult to see how we can do anything other than manage such areas with the ignorance-based world view that Turner outlines.…”
Section: And All Lived Happily Ever After?mentioning
confidence: 99%
“…see Ryder et al 2010). Until we have the additional and targeted investment to support an appropriate level of fundamental and applied research into the ecology and management of our coastal temperate wetlands, it is difficult to see how we can do anything other than manage such areas with the ignorance-based world view that Turner outlines.…”
Section: And All Lived Happily Ever After?mentioning
confidence: 99%
“…Adaptive management frameworks that incorporate BBNs can assist in bridging the science/management divide. This approach facilitates understanding of the knowledge transfer between disciplines, and provides a structure for risk identification, transparency of causal relationships and propagation analyses, and communication (Roux et al, 2006;Ryder et al, 2010). We propose a novel ERA framework that integrates bestpractice BBNs with adaptive management decision making principles ( Fig.…”
Section: Eras At the Science/management Interfacementioning
confidence: 99%
“…In contrast, an evidence-based approach aims to reduce uncertainty and remove bias from decision making processes by basing decisions, on the best available scientific evidence (Sharman and Holmes, 2010). Bayliss et al (2012) concluded that the success of the evidence-based approach can be limited by the lack of effective knowledge transfer between scientist and policy makers, which is further complicated by difficulties in defining what constitutes ''best available science'' (Ryder et al, 2010).…”
Section: Introductionmentioning
confidence: 97%